Determinants of Digital Adaptation among Libyan Students in Malaysian Public Universities during the COVID-19 Pandemic - Mohamed Elhadi M Sharif; Ibrahim Mohamed Yosser; Hamza Masauod M Inbaya (Surman Journal of Science and Technology, 2025)
The rapid shift of higher education to online learning during the COVID-19 crisis transformed higher education and compelled students to quickly adapt to new virtual worlds. For foreign students, this transition brought further hurdles on technology readiness for engagement and unfamiliar training systems. Drawing on the input-process-output conceptual model, the study also investigates digital adaptation among Libyan students in Malaysian public universities with a focus on technological infrastructure and academic engagement as intervening variables. The data in this quantitative research were gathered through a survey as a tool to measure students’ perceptions about their digital learning experience from 110 respondents. Findings: Descriptive findings revealed that students had moderate level of technological access, high academic engagement and positive adaptation to the digital learning. Analysis of correlation showed a strong positive link among three variables that students in favorable technological condition and high participant are prone to cope better with online learning. Regression results also indicated that technological infrastructures and academic engagement were significant predictors of digital adaptation, in which academic involvement exerted stronger predictive power. These findings highlight that dependable technology creates the infrastructure for online learning; students’ motivation, participation and cognitive engagement are even more pivotal to their flexibility. The study has shown the significance of building an enabling digital ecosystem that merges robust ICT infrastructure with instructional practices conducive to interaction and sustained engagement. Such understanding can also support universities in creating effective digital strategies for international learners and for advancing readiness over time for technology-enhanced learning.